A Complicated Case of Serratia marcescens Infective Endocarditis in the Era of the Current Opioid Epidemic. (19th November 2018) - Yeung, Ho-Man; Chavarria, Brijaé; Shahsavari, Dariush
Abstract : While bacteremia due to Serratia marcescens is not uncommon, it rarely causes infective endocarditis. We report an isolated case of a 53-year-old male with history of intravenous drug abuse who presented with multiple acute pain symptoms and was found to have S. marcescens bacteremia with septic emboli in his spleen, brain, and testes, secondary to a large aortic vegetation, as well as aortic infective endocarditis with severe aortic regurgitation requiring aortic valve replacement. His course of disease was further complicated by epidural and psoas abscesses and a necrotic testicle requiring orchiectomy due to his ongoing intravenous drug abuse. This case is an atypical presentation of S. marcescens infection, as he had no overt signs of infection such as fever or significant leukocytosis that are typical of bacteremia, and it also highlights the severity and complicated nature of S. marcescens -infective endocarditis.